2015
DOI: 10.1097/scs.0000000000001402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Torticollis Associated With Plagiocephaly on Infants’ Motor Development

Abstract: The findings suggest that the presence or absence of congenital or acquired torticollis is an important factor that affects gross motor development in infants with plagiocephaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
7
2
2
Order By: Relevance
“…Similar findings, but with other parameters for defining gross motor development (ie, rolling over skill and crawling and sitting without arm support assessed by an experienced physiotherapist and a pediatric neurologist), were reported in a study by Cabrera-Martos et al, 1 revealing that in infants with DP and torticollis, crawling and standing skills were delayed in comparison with infants with DP without torticollis, after adjusting for the severity of DP.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Similar findings, but with other parameters for defining gross motor development (ie, rolling over skill and crawling and sitting without arm support assessed by an experienced physiotherapist and a pediatric neurologist), were reported in a study by Cabrera-Martos et al, 1 revealing that in infants with DP and torticollis, crawling and standing skills were delayed in comparison with infants with DP without torticollis, after adjusting for the severity of DP.…”
Section: Discussionsupporting
confidence: 57%
“…1,9,10 In an earlier study, a prospective follow-up study of 83 infants with congenital torticollis assessed at 2.9 and 12.8 months of age, Schertz et al 9 had found early motor developmental delay in the majority of infants with torticollis at 2.9 months but only in a minority of them at 12.8 months; all were assessed with the Alberta Infant Motor Scale. In a similar study by Ohman et al, 10 a group of children with congenital torticollis, all treated at a department of physiotherapy in a hospital in Sweden, scored significantly lower in motor development assessment at 2 and 6 months of age in comparison to the control group, but there were no differences between the groups at 18 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Its incidence has significantly increased over the past few decades 2 following the recommendation of the American Academy of Pediatrics to place infants in a supine sleeping position to avoid Sudden Infant Death Syndrome. 3 Particularly, the incidence in infants at 7 to 12 weeks of age was estimated to be 46.6% 4 and the prevalence varies between 6.1% and 13.0% at birth, 16.0% and 22.1% at age 6 to 7 weeks, 19.7% at age 4 months, 9.2% at age 8 months, and 6.8% at age 12 months. 5 The risk of PP is increased for infants who required assisted deliveries, are first-born children, are male, have high cumulative exposure to supine positioning, and have neck problems such as infant difficulty turning head, decreased cervical rotation, limited passive cervical rotation, and limited active cervical rotation.…”
mentioning
confidence: 99%
“…There is also some evidence that not treating congenital torticollis and some types of recurrent torticollis may contribute to transient motor asymmetry, motor delay, and plagiocephaly, which would be reversible if addressed properly. [35][36][37] In summary, serious pathology may underlie pediatric torticollis and, thus, should be ruled out first. Following this, conservative manual therapy chiropractic care may be a useful treatment for this condition.…”
Section: Discussionmentioning
confidence: 99%